ASH BIOMASS FOREST: ALTERATION IN THE ATRIBUTES OF ACID SOILS FROM SANTA CATARINA PLATEAU AND EUCALYPTUS PLANTS - SILVA, Franciani Rodrigues; ALBUQUERQUE, Jackson Adriano; GATIBONI, Luciano Colpo; MARANGONI, Jacson Marcelo (Scientia Agraria, 2009)
The industrial process to obtain cellulose generates solid and liquid residues that need viable alternatives to its destination. This work was carried out to evaluate the effect of the application of residues of cellulose and paper industries in Eucalyptus plants on two soils from Santa Catarina plateau. The experiment was done in Lages, Santa Catarina state under greenhouse conditions at the Santa Catarina State University using a Humic Cambisol and a Haplic Nitosol packed in PVC pots with a capacity of 5 dm3. The experimental design was completely randomized with four replicates. The treatments were: No corrective (Test); 3, 6, 12, 18 and 24 t ha-1 of forest biomass ash. Seedlings of Eucalyptus viminalis with 60 days of age were transplanted in the vases and cultivated by 70 days, when they were evaluated soil chemical and physical attributes, the plant dry mass and chemical composition of Eucalyptus shoot. The doses of forest biomass ash neither affect the soil physical attributes nor the soil pH, but it reduced the Al saturation, it elevated the content of K, P, Ca, Mg and the sum for bases of the soils. The ash increased the content of K in the tissue of the shoots of Eucalyptus grown in the Cambisol and the Nitosol and P in the Nitosol, but the other elements and production of dry weight of eucalyptus have not changed.